Method for improving activity of Bayer process red mud through calcination

By calcining the Bayer method red mud at high temperature, the chemical stability of its minerals is damaged and the structure is disordered, the problem of low red mud activity is solved, the feasibility of reactive activity and resource utilization is improved, and it is suitable for red mud from different sources, promoting the preparation of high-performance gelling materials.

CN120247434APending Publication Date: 2025-07-04XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510351392.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In the prior art, the activity of Bayer process red mud is low, which leads to difficulties in resource utilization, especially in the fields of building materials and environmental protection, and the thermal activation process parameters lack universality and universality, making it difficult to apply stably in actual production.

Method used

After drying the Bayer method red mud, it is calcined in a high-temperature furnace and is cooled by air cooling to control the heating rate and temperature range, destroying the chemical stability of silicon and aluminum minerals in the red mud, making its structure disordered, thereby enhancing the reaction activity.

Benefits of technology

It significantly improves the reactivity of red mud, increases the specific surface area and active sites, promotes the decomposition and transformation of mineral phases, and enhances the reaction efficiency of red mud in subsequent reactions. It is suitable for Bayer red mud from different sources, providing a high value-added polymer material preparation path.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120247434A_ABST
    Figure CN120247434A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the activity of Bayer process red mud through calcination. The method comprises the following steps: step 1, selecting Bayer process red mud, drying the red mud, removing free moisture, and grinding to a target particle size; and 2, calcining the dried red mud in a high-temperature furnace, and cooling the red mud to room temperature by air cooling after calcining to obtain the red mud with improved activity. The method has the characteristics of simple process, remarkable effect and wide application range. The calcining treatment can effectively destroy the chemical stability of silicon and aluminum minerals in the red mud, so that the structure is disordered, and the reaction activity of the red mud is remarkably improved. Meanwhile, the method has low dependence on initial components and properties of the red mud, and is suitable for Bayer process red mud from different sources. In addition, the calcined red mud can be further used for preparing a high-added-value geopolymer material through chemical excitation, and a feasible technical path is provided for large-scale resource utilization of the red mud.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of red mud activity, and specifically relates to a method for improving the activity of Bayer red mud by calcination. Background Art

[0002] The aluminosilicate in Bayer red mud has a stable structure and low activity. By changing the chemical composition and microstructure of red mud, it is made more suitable for compatibility with other components, and thus a new aluminosilicate structure is formed through chemical activation. Domestic and foreign scholars have made certain progress in the thermal activation research of red mud, but the composition of red mud varies greatly under different bauxite sources and process conditions, which makes the activation methods and conditions of red mud highly uncertain.

[0003] In the prior art, Liu Shifeng summarized the profound influence of heat treatment conditions on the structure and properties of red mud by studying the physical and chemical changes of red mud before and after heat treatment. The research shows that with the increase of heat treatment temperature, the color, composition and morphology of red mud all change significantly. Specifically, the particle size of red mud particles shows a trend of first decreasing and then increasing with the increase of temperature, which may be due to the rupture and recombination of the surface of red mud particles caused by high temperature; in the lower temperature range, the specific surface area and total pore volume of red mud show an increasing trend, but when the temperature exceeds a certain threshold, these characteristics begin to decline, which may be due to the reduction of pores caused by sintering of particles under high temperature conditions; in addition, the average pore diameter of red mud after heat treatment shows a gradually decreasing trend.

[0004] Li Shaochun et al. studied the influence of different activation methods on the properties of cement-based materials by mechanically activating and thermally activating Bayer red mud respectively. The results show that thermal activation has a more significant effect than mechanical activation. High-temperature treatment causes the dehydroxylation reaction of some minerals in red mud, destroying its stable chemical structure, thus loosening the silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron structures, forming a metastable aluminosilicate structure. The formation of this structure significantly improves the activity of red mud and provides an important basis for the preparation of high-performance cementitious materials. In contrast, although mechanical activation can, to a certain extent, destroy the surface structure of red mud particles, its effect on the internal stable aluminosilicate structure is limited, so the overall effect is not as significant as thermal activation.

[0005] From the existing research results, the low activity problem of red mud has become the key bottleneck restricting its efficient utilization. As an industrial waste residue generated in the alumina production process, red mud has the characteristics of huge output and complex composition. Due to its low natural activity, red mud faces many difficulties in the process of resource utilization, which limits its wide application in the fields of building materials, environmental protection, etc. Therefore, improving the activity of red mud is the primary task to achieve its large-scale resource utilization. Although the above research has achieved certain results in the field of thermal activation, there is still a lack of general thermal activation process parameters and standards for Bayer red mud. This makes it difficult to guarantee the repeatability and universality of the thermal activation process, and the results under different experimental conditions vary greatly, making it impossible to be stably applied in actual production.

[0006] In addition, the thermal activation mechanism has not been fully clarified. Especially, there is a lack of systematic research on the migration paths and reaction behaviors of various mineral oxides and potential heavy metals in red mud during the thermal activation process. This lack of understanding makes it difficult to accurately evaluate the stability of the products after thermal activation and the potential environmental risks that may be caused during the application process. Summary of the Invention

[0007] In order to overcome the above defects existing in the prior art, the purpose of the present invention is to provide a method for improving the activity of Bayer red mud by calcination. This method has the characteristics of simple process, remarkable effect and wide application range. Calcination treatment can effectively destroy the chemical stability of silicon and aluminum minerals in red mud, disorder its structure, and thus significantly improve the reaction activity of red mud. At the same time, this method has a low dependence on the initial composition and properties of red mud and is applicable to Bayer red mud from different sources. In addition, the calcined red mud can be further prepared into high-value-added geopolymer materials through chemical activation, providing a feasible technical path for the large-scale resource utilization of red mud.

[0008] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0009] A method for improving the activity of Bayer red mud by calcination, comprising the following steps;

[0010] Step 1, select Bayer red mud, dry the red mud to remove free moisture, and grind it to the target particle size;

[0011] Step 2: Place the dried red mud in a high-temperature furnace for calcination. After the calcination is completed, cool the red mud to room temperature by air cooling to obtain the red mud with improved activity.

[0012] In Step 1, the selected red mud from the Bayer process has a slightly higher calcium content. The components are specifically in the following mass ratios: Fe2O3: 10 - 30%; Al2O3: 20 - 30%; SiO2: 20 - 30%; CaO: 15 - 25%; TiO2: 2 - 10%; Na2O: 2 - 6%; Others: 1 - 5% (MgO, K2O).

[0013] Step 1 is specifically the following operating steps: Step (1): Evenly spread the red mud sample on a tray with a thickness not exceeding 2 cm to ensure uniform drying; preheat the oven:

[0014] Step (2): Preheat the oven to 105°C and keep the temperature stable during the drying process;

[0015] Step (3): Put the selected red mud into the oven and start timing; during the drying process, the red mud can be turned over every once in a while (such as every 6 hours) to ensure uniform drying.

[0016] Step (4): End the drying: After 24 hours, turn off the oven and take out the red mud; put the dried red mud into a desiccator to cool to room temperature to avoid moisture absorption. In Step 1, the target particle size is 50 - 300 μm. This range achieves a balance among activity, cost, and process feasibility and is suitable for most industrial applications.

[0017] Step 2 is specifically as follows:

[0018] Calcine at a set temperature of 800 - 1000°C for a certain time of 2 - 4 hours, and control the heating rate at 10 - 15°C / min during the calcination process.

[0019] Furthermore, calcine at a set temperature of 1000°C for a certain time of 4 hours, and control the heating rate at 10°C / min during the calcination process.

[0020] The conditions defined in Step 2 are specifically as follows:

[0021] Initial temperature of red mud: 800°C - 1000°C; Target temperature: room temperature (25°C); Cooling equipment: axial flow fan + cooling tunnel; Air volume: 1000 CFM; Cooling time: 20 - 30 minutes; Temperature monitoring: Infrared thermometer continuously monitors the temperature of the red mud; Collection method: The cooled red mud is sent to a storage bin through a conveyor belt.

[0022] Some mineral phases in the red mud with enhanced activity (such as cancrinite, hematite, etc.) will undergo phase transformation or decomposition, generating new active phases, further enhancing the chemical activity of the red mud. Silicon and aluminum minerals transform from ordered crystals to amorphous SiO2 and Al2O3. These amorphous substances have characteristics such as high specific surface area, high reactivity, porosity, and low thermal stability, significantly improving the adsorption, catalytic, and gelling properties of the red mud, providing an important basis for its resource utilization. The amorphous alumina (Al2O3) and amorphous silica (SiO2) in the calcined red mud provide active sites.

[0023] After calcination, the silicon dissolution rate in the red mud is 3 - 70 mg / L, and the aluminum dissolution rate is 73 - 300 mg / L.

[0024] The characteristics of the finally obtained red mud with enhanced activity are as follows: Thermal activation destroys the crystal structure of silicon and aluminum minerals in the red mud, transforming them from ordered crystals to amorphous forms, significantly enhancing the reactivity of the red mud. Calcination and subsequent grinding treatment refine the red mud particles, significantly increasing the specific surface area and providing more active sites for subsequent chemical reactions. The dissolution rates of elements such as silicon and aluminum in the thermally activated red mud increase, making it easier to react with activators to form geopolymers or other gelling materials. During the thermal activation process, some mineral phases in the red mud (such as cancrinite, hematite, etc.) will undergo phase transformation or decomposition, generating new active phases, further enhancing the chemical activity of the red mud. The thermally activated red mud has higher stability and can adapt to different environmental conditions, providing a basis for preparing high-performance all-solid waste red mud-based gelling materials.

[0025] The beneficial effects of the present invention:

[0026] After thermal activation treatment, the dissolution rate of aluminum ions in the red mud significantly increases from 72 mg / L to 246 mg / L, indicating that the chemical activity of the red mud has been greatly improved. The direct effect of this improvement is that the reaction efficiency of the red mud in subsequent reactions is significantly enhanced, enabling it to react more fully with activators to prepare red mud-based gelling materials with relatively excellent properties.

[0027] During the reaction process, thermal activation destroys the stable crystal structure of silicon and aluminum minerals in the red mud, transforming them into amorphous forms, and at the same time promoting the decomposition and transformation of mineral phases, releasing more active silicon and aluminum components.

[0028] These active components quickly dissolve in an alkaline environment to form silicate (SiO4 4- ) and aluminate (AlO4 5-)Ions, and then through polycondensation reaction to generate geopolymers gel with a three-dimensional network structure. During the thermal activation process of red mud, its complex mineral structure will also change. Common minerals in red mud, such as gibbsite (Al(OH)3), boehmite, etc., will undergo dehydration reactions when heated.

[0029] As the temperature increases, the crystal structure of the generated alumina gradually transforms into a more active amorphous or metastable structure, and the coordination environment around the aluminum ions changes, making it easier for them to break away from the lattice and participate in the reaction in subsequent reactions. At the same time, some silicate minerals in red mud, such as cancrinite (Na6Ca2Al6Si6O 24 (CO3)2), etc., under the action of heat, the network structure composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons will also break and rearrange, exposing more active sites of aluminum ions, creating conditions for subsequent reactions with other substances. This process not only improves the reaction rate but also significantly improves the mechanical properties and durability of the final material.

[0030] The present invention significantly improves the activity of red mud through thermal activation, provides reliable technical support for the efficient resource utilization of red mud, and at the same time reduces the negative impact of red mud stacking on the environment, having important environmental protection and economic value. Brief Description of the Drawings

[0031] Figure 1 Schematic diagram of the activity index of red mud activated at different calcination temperatures.

[0032] Figure 2 XRD patterns of Bayer red mud at different calcination temperatures.

[0033] Figure 3 Infrared diagrams at different calcination temperatures.

[0034] Figure 4 Leaching diagrams of active silicon and aluminum in red mud at different calcination temperatures.

[0035] Figure 5 XRD patterns of Bayer red mud at different calcination times.

[0036] Figure 6 FTIR diagrams of red mud at different calcination times.

[0037] Figure 7 Leaching rate diagrams of silicon and aluminum ions in red mud at different calcination times. Detailed Description of the Invention

[0038] The present invention will be further described in detail below with reference to the drawings.

[0039] Example 1: Calcination at 800 °C to improve the adsorption activity of red mud;

[0040] The red mud components selected in this example are: Fe2O3: 19%; Al2O3: 25%; SiO2: 25%; CaO: 18%; TiO2: 5%; Na2O: 3%, others: 5% (including MgO, K2O, etc.).

[0041] Calcination conditions:

[0042] Temperature: 800 °C;

[0043] Time: 2 hours;

[0044] Atmosphere: air;

[0045] Treatment process:

[0046] Dry the Bayer red mud to constant weight and grind it to 100 - 200 μm.

[0047] Put the red mud into a muffle furnace and heat it to 800 °C at a heating rate of 5 °C / min, and hold for 2 hours.

[0048] Air-cool to room temperature to obtain calcined red mud.

[0049] Application direction: Used as an adsorbent in wastewater treatment.

[0050] Example 2: Calcination at 900 °C to improve the gelling activity of red mud

[0051] The red mud components selected in this example are: Fe2O3: 20%; Al2O3: 24%; SiO2: 26%; CaO: 17%; TiO2: 6%; Na2O: 2%, others: 5% (including MgO, K2O, etc.).

[0052] Calcination conditions:

[0053] Temperature: 900 °C;

[0054] Time: 3 hours;

[0055] Atmosphere: air;

[0056] Treatment process:

[0057] Dry and grind the red mud to 50 - 100 μm.

[0058] Put the red mud into a muffle furnace and heat it to 900 °C at a heating rate of 10 °C / min, and hold for 3 hours.

[0059] Quickly cool to room temperature to obtain calcined red mud.

[0060] The gelling activity of the calcined red mud is significantly improved and can be used as a cement admixture to replace part of the cement.

[0061] Application direction:

[0062] Active admixtures for building materials (such as cement, concrete).

[0063] Example 3: Roasting at 1000°C to improve the metal recovery rate of red mud

[0064] The red mud selected in this example has the following components: Fe2O3: 21%; Al2O3: 25%; SiO2: 26%; CaO: 17%; TiO2; 6%; Na2O: 2%, others: 3% (including MgO, K2O, etc.). Roasting conditions:

[0065] Temperature: 1000°C;

[0066] Time: 4 hours;

[0067] Atmosphere: air;

[0068] Treatment process:

[0069] Dry the red mud and grind it to 200 - 300 μm.

[0070] Put the red mud into a muffle furnace and heat it to 1000°C at a heating rate of 10°C / min, and keep it warm for 4 hours.

[0071] Cool naturally to room temperature to obtain roasted red mud.

[0072] Application directions:

[0073] For metal recovery (such as extraction of iron, aluminum, titanium).

[0074] Effect of roasting temperature on the activity of Bayer red mud:

[0075] 1 The activity index of Bayer red mud is significantly improved

[0076] Taking the compressive strength of the cementitious material mortar prepared from red mud and cement as the index to evaluate the pozzolanic activity of red mud, Figure 1 reveals the change trend of the pozzolanic activity index of red mud under different temperature conditions. It can be analyzed from the figure that the pozzolanic activity index of Bayer red mud shows a trend of first increasing, then decreasing, then increasing again and then decreasing at different temperatures. Among them, the 7-day activity index reaches the highest of 88% at a roasting temperature of 900°C. The 28-day activity index of the red mud activated at this temperature is 77%, ranking second (only 1% lower than the highest activity index of 78%). The 7-day activity index can reach 87% at 500°C, and the 28-day activity index reaches the highest of 78%. It can be seen from this that when the activation temperature is 500°C and 900°C, the activity index of the activated Bayer red mud is basically the same. The highest 28-day activity index of the activated red mud is 9% higher than that of the original unthermally activated Bayer red mud, indicating that the activity of the thermally activated Bayer red mud has been significantly improved.

[0077] The active mineral phases of Bayer red mud increase

[0078] Figure 2 shows the changes in the mineral phase structure of thermally activated Bayer red mud at different calcination temperatures. By analyzing Figure 2 it can be concluded that the main mineral phases of the uncalcined and activated red mud are cancrinite, chlorite, quartz, bayerite, katoite, calcite, and diaspore; the red mud calcined at 500 °C will form hydrogarnet, and the red mud calcined at 800 °C will form nepheline, zeolite (Na6(AlSiO4)), and gehlenite. The red mud calcined at 1200 °C will produce other crystal phases.

[0079] In the low-temperature heat treatment stage (100 °C - 400 °C), some minerals in the red mud begin to decompose or undergo phase changes. The characteristic peak of katoite completely disappears at 400 °C, indicating that it loses some surface hydroxyl groups under high temperature and transforms into hydrogarnet. At the same time, the characteristic peak of bayerite also completely disappears at 400 °C, indicating that it is completely dehydrated. The characteristic peak of diaspore slightly decreases when approaching 400 °C, and as the temperature further rises to 500 °C, its characteristic peak completely disappears, indicating that diaspore is transformed into amorphous alumina. In addition, the crystal structure of chlorite begins to degrade at 400 °C, and its characteristic peak completely disappears at 500 °C, indicating that its structure is completely destroyed.

[0080] In the medium-temperature heat treatment stage (500 °C - 800 °C), the carbonate minerals and some silicate minerals in the red mud decompose significantly. The characteristic peak of calcite gradually weakens with the increase of temperature and completely disappears at 800 °C, indicating that calcite completely decomposes at this temperature. The characteristic peak of cancrinite continuously weakens during heating and completely disappears at 800 °C. During this process, cancrinite loses bound water and carbonate radicals and transforms into nepheline and some zeolites. In addition, the hydroxyl groups in hydrogarnet gradually lose water at 800 °C and finally transform into gehlenite.

[0081] In the high-temperature heat treatment stage (900 °C - 1200 °C), the mineral phase changes in the red mud are further intensified. The content of gehlenite reaches the maximum value at 900 °C, then gradually decreases and completely disappears at 1200 °C. Quartz shows high stability in a high-temperature environment and does not start to decompose until 1100 °C. Nepheline decomposes at 1100 °C, and the content of zeolite reaches the maximum value at 1100 °C. It should be noted that hematite (Fe2O3) shows good stability throughout the heat treatment process and still exists until 1100 °C and completely disappears at 1200 °C.

[0082] When the temperature rises to 1200 °C, magnetite also appears. At this temperature point, some sintering and melting phenomena will also occur, and some minerals will further undergo solid-phase reactions or form glass phases, resulting in changes in the types and contents of mineral phases again. For example, some minerals with low melting points may start to melt and fuse with the surrounding minerals to form new complex mineral phases or vitreous substances.

[0083] Based on the comprehensive XRD analysis results, it is found that when the calcination temperature is 1000 °C, the transformation, decomposition and other changes of the minerals inside the red mud reach a relatively ideal equilibrium state. The specific manifestations are as follows: Hematite still maintains a high crystallinity, providing a certain structural stability; the content of gehlenite is close to the maximum value, indicating that the active phase of aluminosilicate minerals reaches a high level; the existence forms and contents of minerals such as quartz and zeolite are in an optimized state. This equilibrium state of mineral phases enables the red mud to exhibit excellent activity performance in subsequent applications, which may be closely related to the formation of specific mineral phases, the optimization of crystal structures, and the change of element existence forms. To sum up, the mineral changes of red mud at different heat treatment temperatures show certain rules. In particular, the transformation and disappearance of some minerals reflect the significant influence of temperature on mineral structures. These changes not only help to deeply understand the heat treatment process of red mud, but also provide a theoretical basis for its subsequent utilization.

[0084] 3 The fracture and recombination of Si-O-Si(Al) molecular bonds in Bayer red mud

[0085] The FTIR method can analyze the changes in the Si-O-Si(Al) molecular bonds in the material. Therefore, in this study, FTIR was used to detect the chemical structure changes of the red mud precursor activated at different temperatures, so as to better analyze the activity of the red mud precursor activated at different temperatures. Figure 3 The Fourier transform infrared spectroscopy (FT-IR) spectra of red mud thermally activated at different temperatures are shown.

[0086] Figure 3 In [the figure], it is usually corresponding to the stretching vibration of hydroxyl groups (-OH) near the wavenumber of 3660 cm -1 As the temperature rises from 100 to 400 °C, the peak intensity at this wavenumber gradually weakens, indicating that some hydroxyl-containing minerals in the red mud, such as katoite, begin to lose surface hydroxyl groups, which is in line with the result that katoite in XRD transforms into hydrogarnet at 400 °C. From 400 to 800 °C, the peak intensity further decreases, and the hydroxyl groups in minerals such as hydrogarnet continue to decrease. After 800 °C, the peak at this wavenumber almost disappears, meaning that most of the hydroxyl groups in the red mud have been removed. At 3448 cm -1Generally attributed to the stretching vibration of associated hydroxyl groups. In the low-temperature stage of 100 - 400 °C, the peak intensity slowly decreases, reflecting the reduction in the number of associated hydroxyl groups within the mineral lattice or between layers in the red mud. At 500 - 800 °C, the rate of peak intensity decrease accelerates, corresponding to the degradation of mineral structures such as chlorite and a significant reduction in associated hydroxyl groups. At 800 - 1200 °C, the peak intensity is weak and tends to be stable, indicating that the remaining associated hydroxyl groups are in a relatively stable mineral structure. 1646 cm -1 Related to the H - O - H bending vibration of water molecules. At 100 - 500 °C, the peak intensity significantly decreases, indicating that the adsorbed water and some mineral crystal water in the red mud are gradually removed. At 500 - 800 °C, the peak further weakens. By 800 °C, the peak intensity is already extremely low, indicating that the water molecule content in the red mud is extremely small at this time, which is consistent with the process of calcite, cancrinite, and other minerals decomposing and losing crystal water and bound water. 1436 cm -1 Often related to the symmetric stretching vibration of carbonate groups. At 100 - 800 °C, the peak intensity continuously weakens, indicating that carbonate-containing minerals in the red mud, such as calcite and cancrinite, gradually decompose with increasing temperature, releasing carbon dioxide and resulting in a reduction in the number of carbonate groups. At 800 °C, the peak at this wavenumber basically disappears, confirming that minerals such as calcite have completely decomposed and a large amount of carbonate has escaped. The absorption peak near 1110 cm-1 is related to the Si - O bond and disappears after thermal activation at 700 °C, mainly reflecting a significant change in the chemical environment or mineral phase of the silicon - oxygen bond (Si - O) in the red mud, which may be related to the decomposition of hydrogarnet. 985 cm -1 Corresponds to the stretching vibration of the Si - O bond. Throughout the temperature range of 100 - 1200 °C, the position of the peak is basically stable, but the intensity gradually increases at 100 - 1000 °C, indicating that with increasing temperature, the silicon - oxygen bond participates in the formation of more stable mineral structures, such as gehlenite. After 1000 °C, the peak intensity slightly decreases, possibly due to the rearrangement or decomposition of some Si - O structures at high temperatures. 870 cm -1 Generally related to the vibration of the Al - O bond. At 100 - 500 °C, as aluminous minerals such as gibbsite and diaspore transform, the peak intensity changes. At 500 - 1000 °C, the peak intensity gradually increases, suggesting the formation of more stable mineral phases containing the Al - O bond, such as the transformation of amorphous alumina into a more ordered aluminous mineral structure, which coincides with the stage of increased red mud activity. At 1000 - 1200 °C, the peak intensity is basically stable, indicating that the aluminum - oxygen bond remains relatively stable in the mineral structure in this temperature range. 685 cm -1 May be related to the Fe - O bond vibration. At 100 - 1100 °C, the peak intensity is relatively stable, reflecting the stable structure of iron-containing minerals such as hematite (Fe2O3). At 1100 - 1200 °C, as hematite gradually disappears, the peak intensity also weakens, indicating a reduction in the number of Fe - O bonds.

[0087] At 1000 °C, the mineral structure is adjusted to a relatively ideal state, providing a structural basis for the improvement of the red mud activity and further corroborating the conclusion that the red mud has the best activity at this temperature. The X-ray diffraction (XRD) results show that in the Bayer red mud precursor after thermal activation, part of the katoite and gibbsite decompose during the heat treatment process, generating SiO2 and Al2O3 with higher activity. The infrared spectroscopy (FTIR) analysis results further indicate that the Si-O bond and Al-O bond in the red mud precursor after thermal activation are broken, and the degree of polymerization of the structure decreases, thereby improving the reaction activity of the red mud.

[0088] 4 Increase in the leaching of active silicon and aluminum from Bayer red mud

[0089] Figure 4 (a) and (b) are the leaching concentrations of Si and Al ions in Bayer red mud under different thermal activation temperature conditions measured by ICP method and chemical titration method respectively. From Figure 4 (a), it can be seen that as the thermal activation temperature gradually increases, the dissolution amounts of silicon and aluminum ions in the red mud show a changing pattern of first decreasing, then increasing, and then decreasing. Especially under the thermal activation treatment at 300 - 600 °C, the concentrations of silicon and aluminum ions in the red mud show almost no significant change compared with the red mud dried at 100 °C. It should be noted that when the thermal activation temperature reaches 700 - 1000 °C, the concentration of Al 3+ increases significantly, and the dissolution amount of silicon ions also increases, although the increase amplitude of silicon ions is relatively small. In the red mud after thermal activation treatment at 1000 °C, the leaching concentrations of both silicon and aluminum ions reach the peak values, which are significantly higher than those of the red mud treated at other temperatures, showing a significant increase in the order of magnitude. However, this result is somewhat contradictory to the conclusion of the activity index test. It should be noted that in the relevant research on the activity index, it is mentioned that the presence of Al 3+ does not necessarily have a positive promoting effect on the activity index. The red mud itself is rich in aluminum elements. After thermal activation treatment, the aluminum elements can be dissolved out with high efficiency, which provides a valuable source of activity for the subsequent utilization of the red mud. To sum up, after the red mud is thermally activated at 1000 °C, the dissolution amounts of its Si and Al ions are significantly higher than those of the red mud heat-treated at other temperatures, indicating that the activated red mud at this temperature shows higher activity.

[0090] According to Figure 4 (b) analysis, the concentration of Si 4+ shows an upward trend with the increase of temperature. When the temperature reaches 800 °C, the concentration of Si 4+ reaches the peak value, and the leaching rate is 15.3%; while at 100 °C, the leaching rate is 13.13%. The difference between the two is only 2%, indicating that the change in temperature has a relatively small effect on the leaching rate of Si 4+ . At the same time, the concentration of Al 3+The concentration also showed a similar trend, reaching the highest value at 900 °C with a leaching rate of 27.42%; while at 100 °C, the leaching rate was 21.54%. The maximum difference in the leaching rates between the two was 6%, and the data fluctuation range was also small. As the activation temperature of the red mud increased, the leaching amount of silicon and aluminum ions showed a slow growth trend. Generally speaking, the dissolution amount of aluminum was significantly higher than that of silicon, mainly because the dissolution temperature of silicon in the Bayer red mud used in this experiment was relatively high. Therefore, the main source of activity in the red mud was the active Al2O3 released by the mineral decomposition.

[0091] Effect of Calcination Time on the Activity of Bayer Red Mud

[0092] 1 Increase in Active Mineral Phases of Bayer Red Mud

[0093] Figure 5 It is the XRD analysis results of Bayer red mud under different calcination time conditions at a thermal activation temperature of 1000 °C.

[0094] From Figure 5 Analysis shows that regardless of the change in calcination time, the main phase structure in the red mud has not changed significantly. Specifically, the main phases in the thermally activated red mud include cancrinite (Na6Ca2Al6Si6O 24 (CO3)2·2H2O), as well as nepheline (NaAlSiO4) and zeolite (Na6(AlSiO4)6) formed by the decomposition of cancrinite. In addition, gehlenite (Ca2Al2SiO7) also appears in some samples, while quartz and hematite always exist in the samples. It can be seen from the XRD pattern that these stable phases are consistent with the results of the active silicon and aluminum leaching titration test. As the calcination time prolongs, the characteristic diffraction peak of zeolite gradually strengthens. At the same time, the characteristic peak of gehlenite is relatively weak, suggesting that other reactions may also occur during this period. It should be noted that the formation of minerals such as zeolite, gehlenite, and nepheline are all products of the cancrinite decomposition process, and these products are the main sources of active silicon and aluminum in the red mud system. Especially when the calcination time reaches 4 hours, the characteristic peaks of the three main minerals are relatively obvious, indicating that 4 hours is the optimal condition for red mud calcination. At this time, the activation degree of the red mud system reaches the highest, further verifying that this time point is the optimal calcination time. However, based on the above analysis results, the mineral phase changes of the red mud after calcination for 4 hours and 2 hours are not very different. It is speculated that in industrial applications, choosing 2 hours of calcination as the appropriate time will help obtain the best activation effect and performance. This discovery not only provides an important basis for understanding the chemical transformation process of red mud, but also provides useful guidance for its potential application in industrial production.

[0095] 2 Breaking and Recombination of Si-O-Si(Al) Molecular Bonds in Bayer Red Mud

[0096] Figure 6 Infrared spectrum analysis of Bayer red mud activated at different calcination times shows that Figure 6 distinct characteristic absorption peaks can be clearly observed in the infrared region. During the activation process of Bayer red mud at different calcination times, a series of unique absorption peaks emerge, reflecting changes in its structure and composition. First, near the wavenumber of 3448 cm-1, a broad absorption peak appears, mainly caused by the stretching vibration of the O-H bond in water molecules. This absorption peak shows a certain superposition effect, suggesting that water molecules in the red mud sample may exist in multiple different structural states. Further analysis reveals that the weaker absorption peak at 1633 cm-1 mainly stems from the bending vibration of the O-H bond

[66] , indicating that even after high-temperature calcination, the bound water in the red mud powder is still a non-negligible component. This bound water plays an important role in various chemical reactions and physical changes, having a profound impact on the final properties of the material. In addition, in the sample calcined for 1 hour, a weak absorption peak appears at the wavenumber of 1437 cm-1, corresponding to the asymmetric stretching vibration of the O-C-O bond. Notably, this absorption peak disappears after the calcination time is extended to 2 hours and above, indicating that the decomposition process of calcite in the red mud is completed within 1 hour. At the wavenumber of 983 cm-1, another obvious absorption peak appears, attributed to the symmetric stretching vibration of the Si-O bond. Si-O bonds usually participate in complex chemical reaction processes, and the appearance of this absorption peak reveals the chemical characteristics of silicon oxides in the red mud. Further observation shows that the absorption peak near the wavenumber of 611 cm-1 is also caused by symmetric stretching vibration, indicating the presence of other metal oxides in the red mud. As the calcination time increases, especially in the red mud samples calcined for more than 2 hours, the absorption peak in the wavenumber range of 676 - 611 cm-1 gradually shows the characteristics of the symmetric stretching vibration of the Si-O-T (T = Al, Si) bond. These Si-O-T bonds are of great significance in materials science and mineralogy and can affect the structure, chemical stability, and reactivity of materials. In the 470 cm-1 band, the bending vibration of the Si-O-Si and O-Si-O bonds leads to the appearance of the absorption peak, further proving the presence of chemical bonds of elements such as silicon and aluminum in the red mud sample and revealing the possible interactions of these chemical bonds in the formation of a stable structure.

[0097] 3 Increase in the leaching of active silicon and aluminum from Bayer red mud

[0098] Figure 7 (a) shows the leaching rates of silicon and aluminum in red mud calcined at 1000 °C for 1 - 5 hours measured by the ICP method. As can be seen from the figure, as the thermal activation time increases, the concentration of Al in the red mud 3+ undergoes a process of first increasing and then decreasing. This indicates that in the initial stage, due to the influence of thermal activation, Al 3+The solubility increases, leading to a significant rise in its concentration; however, as time goes on, this trend gradually weakens and finally stabilizes. Specifically, when the thermal activation time reaches 4 hours, the concentration of Al in the red mud 3+ reaches a peak value of approximately 270.9 mg / L. Compared with Al 3+ , the solubility change of Si 4+ is relatively slow, showing an overall slow upward trend, but the concentration change is not significant. Compared with the red mud without thermal activation, the thermally activated red mud shows a higher dissolution rate of silicon and aluminum ions, indicating that thermal activation treatment helps to promote the release of active silicon and aluminum in the red mud. It is worth noting that although the concentration changes of silicon and aluminum ions are relatively stable during the entire thermal activation process, extending the calcination time does not seem to have a significant effect on improving the dissolution effect of silicon and aluminum. This may mean that in practical applications, choosing the appropriate thermal activation time point may be more important than simply extending the calcination time.

[0099] Figure 7 (b) shows the leaching rate of active silicon and aluminum components measured by chemical titration after calcining the red mud at a high temperature of 1000 °C for 1 - 5 hours. It can be seen that as the thermal activation time extends, the concentration of Al in the red mud 3+ initially shows an increasing trend, but then starts to decline. Especially when the thermal activation time reaches 4 hours, the leaching rate of aluminum increases significantly, with a maximum value of up to 27.83%. At the same time, for the leaching rate of Si 4+ , the situation is slightly different. The leaching rate of this ion does not show the same linear upward trend as Al, but shows a slow and stable increase process, accompanied by a gradually decreasing tendency. However, at a calcination time of 3 hours, the leaching rate of Si reaches a maximum value of 13.13%. It is worth noting that within the different calcination times set in this chapter's research, the leaching rate of Si does not show a significant change trend.

[0100] Comprehensive analysis reveals that although the thermal activation time has an impact on the chemical conversion effect and leaching rate of red mud, the overall trend indicates that this impact does not reach the expected significant level. Possible reasons include the inherent properties of red mud and minor errors in the experimental operations. To obtain the leaching rate of silicon and aluminum components more precisely, the research should also conduct more in-depth analysis in combination with other detection methods. Combining the analysis of XRD, FTIR, and the silicon-aluminum leaching test results, the influence of the calcination time on the mineral phase of red mud changes less. Compared with the red mud without calcination activation, the active silicon and aluminum in the calcined red mud are effectively dissolved, thus significantly enhancing its activity. Appropriately extending the calcination time of thermally activated red mud helps to further improve its activity, but the effect of increasing the activity gradually weakens when the calcination time is too long. Based on the above analysis and considering energy conservation and environmental protection, this application selects 2 hours as the calcination time of thermally activated red mud to achieve a better activity improvement effect while reducing energy consumption.

[0101] This invention obtains the influence of the thermal activation temperature and thermal activation time on the phase change and activity of Bayer red mud. The active silicon and aluminum dissolution method is used to test the dissolution of active silicon and aluminum in Bayer red mud at different temperatures and different thermal activation times, and XRD, FTIR and other means are used to analyze the phase change and chemical bond change of red mud with the thermal activation time.

[0102] The main conclusions obtained by this invention are as follows:

[0103] (1) With the increase of the activation temperature, a series of changes occur in the mineral phase of red mud. Specifically, at 400 °C, katoite transforms into hydrogarnet; at 500 °C, diaspore disappears and transforms into amorphous alumina; at 800 °C, cancrinite completely decomposes to form nepheline and zeolite, and at the same time hydrogarnet decomposes to form gehlenite. The contents of zeolite and gehlenite reach the maximum at 1000 °C, which helps to increase the active silicon and aluminum in red mud.

[0104] (2) The pozzolanic activity index shows that thermal activation significantly enhances the cementitious activity of red mud. The pozzolanic activity of red mud first increases and then decreases with the increase of the heat treatment temperature, and the activity index reaches the highest value at 500 °C, and the 28-day pozzolanic activity is 71%. However, when the temperature rises to 800 °C, the 28-day activity drops to 52%. At 800 °C, due to the limited content of gypsum in the cement, the active SiO2 and Al2O3 in the cement-red mud composite sample can only react with portlandite to form C-A-H or C-A-S-H gels, and AFt in the sample gradually transforms into AFm, resulting in the decrease of the pozzolanic activity of red mud at this temperature.

[0105] (3) The red mud before activation and after activation at different temperatures all has active silicon and aluminum ions. By combining the ICP measurement of ion concentration and the chemical titration method to measure the ion leaching rate, it is found that the dissolution amount of silicon and aluminum ions is relatively large at 700 - 1000 °C, and the red mud has higher activity. At the same time, it is found by comparison that the ICP method for measuring ion concentration has higher accuracy and can more clearly see the change trend of silicon and aluminum ions in the red mud.

[0106] (4) Under different calcination times, the phase change of the red mud is small, and the XRD and FTIR analysis results show a similar trend. The XRD pattern shows that the mineral phase structure of the red mud is basically the same, mainly including cancrinite, nepheline, zeolite, gehlenite, quartz and hematite. These mineral phases indicate that the calcination time has little effect on the mineral composition of the red mud, and the main components remain stable. During the calcination process, the breakage and recombination of Si - O and Al - O bonds promote the release of more active SiO2 and Al2O3.

[0107] (5) With the increase of the thermal activation time, the dissolution amounts of silicon and aluminum in the red mud show a trend of first increasing and then decreasing, indicating that the thermal activation process has a significant impact on the dissolution of silicon and aluminum. During the thermal activation time of 3 to 4 hours, the dissolution amounts of silicon and aluminum increase. The ICP analysis results show that when the calcination time is 4 hours, the dissolution concentration of aluminum reaches the highest value of 270.9 mg / L. This indicates that a thermal activation time of 4 hours may help improve the dissolution efficiency of aluminum and silicon in the red mud. However, considering the XRD, FTIR analysis and the dissolution of silicon and aluminum, the effect of the calcination time on the improvement of the red mud activity is not significant. Considering the industrial production requirements and energy conservation and environmental protection factors, a calcination time of 2 hours was selected for subsequent research.

Claims

1. A method for improving the activity of Bayer red mud by calcination, characterized in that, It includes the following steps; Step 1: Select Bayer red mud, dry the red mud to remove free moisture, and grind it to the target particle size; Step 2: Place the dried red mud in a high-temperature furnace for calcination. After the calcination is completed, cool the red mud to room temperature by air cooling to obtain the red mud with improved activity.

2. The method for improving the activity of Bayer red mud by calcination according to claim 1, characterized in that, In Step 1, the selected Bayer red mud has a slightly higher calcium content. The components are specifically in a mass ratio of: Fe2O3: 10 - 30%; Al2O3: 20 - 30%; SiO2: 20 - 30%; CaO: 15 - 25%; TiO2: 2 - 10%; Na2O: 2 - 6%; Others: 1 - 5% (MgO, K2O).

3. A method for improving the activity of Bayer red mud by calcination according to claim 2, characterized in that, The specific operation steps of Step 1 are as follows: Step (1): Spread the red mud sample evenly on a tray with a thickness not exceeding 2 cm to ensure uniform drying; Preheat the oven: Step (2): Preheat the oven to 105°C and keep the temperature stable during the drying process; Step (3): Put the selected red mud into the oven and start timing; During the drying process, the red mud can be turned over every once in a while to ensure uniform drying. Step (4): End drying: After 24 hours, turn off the oven and take out the red mud; Put the dried red mud into a desiccator and cool it to room temperature to avoid moisture absorption. In Step 1, the target particle size is 50 - 300 μm. This range achieves a balance among activity, cost, and process feasibility and is suitable for most industrial applications.

4. A method for improving the activity of Bayer red mud by calcination according to claim 1, characterized in that, The specific content of Step 2 is as follows: Calcine at a set temperature of 800 - 1000°C for a certain time of 2 - 4 hours, and control the heating rate at 10 - 15°C / min during the calcination process.

5. A method for improving the activity of Bayer red mud by calcination according to claim 4, characterized in that, The specific conditions defined in Step 2 are as follows: Initial temperature of red mud: 800°C - 1000°C; Target temperature: room temperature; Cooling equipment: axial flow fan + cooling tunnel; Air volume: 1000 CFM; Cooling time: 20 - 30 minutes; Temperature monitoring: Infrared thermometer monitors the temperature of red mud in real time; Collection method: The cooled red mud is sent to a storage bin through a conveyor belt.

6. A method for improving the activity of Bayer red mud by calcination according to claim 4, characterized in that The amorphous alumina and amorphous silica in the calcined red mud provide active sites.

7. A method for improving the activity of Bayer red mud by calcination according to claim 4, characterized in that, The silicon dissolution rate in the calcined red mud is 3 - 70 mg / L, and the Al dissolution rate is 73 - 300 mg / L.

Citation Information

Cited By

  • Method for preparing cementing material from thermally activated and modified red mud

    CN120136518A